Design of 1SGL-240 type sugarcane deep-soiling soil preparation machine. (November 2020) - Wei, Lijiao; Li, Ming; Ge, Chang; Huang, Weihua; Niu, Zhaojun; Zhu, Xianchong
Abstract: Aiming at the problems of low efficiency and high energy consumption in the process of sugarcane planting, as well as the problems of soil compaction and hardening caused by tractor repeatedly entering the field and rolling sugarcane field, this paper designed a kind of combined soil preparation machine with reasonable structure and conforming to the continuous planting conditions of sugarcane field in China by optimizing the combination of key components. The tractor drives the machine into the field once, which can complete the processes of deep loosening, loosening the head of sugarcane, ridging and soil preparation. In this paper, the overall mechanism of the machine, subsoiling parts, pulling wheel, ridging mechanism and other key components are designed and analyzed, and the performance of the machine is evaluated through field test. The results showed that: the process of soil entry and subsoiling was stable, the rate of pulling out sugarcane head reached 91.2%, and all properties met the requirements of sugarcane field.